Knowledge domain and emerging trends in beta‐cell research: A bibliometric and knowledge‐map analysis - Luo, Yunpeng; Wang, Tong; Chen, Zhuhong; Zhang, Guangde (Frontiers in Endocrinology, 2023)
Background: Up to now, the physiology, pathology, and recovery of beta-cells have been intensively studied and made great progress, and these are of major significance for the treatment of related diseases. Nevertheless, a comprehensive and objective report on the status of beta-cell research is lacking. Therefore, this study aims to conduct a bibliometric analysis to quantify and identify the current status and trending issues in beta-cell research. Methods: The articles and reviews related to beta-cell were obtained from the Web of Science Core Collection on August 31, 2022. Two scientometric software (CiteSpace 6.1.R3 and VOSviewer 1.6.18) were used to perform bibliometric and knowledge-map analysis. Results: A total of 4098 papers were published in 810 academic journals in 2938 institutions from 83 countries/regions. The number of beta-cell-related publications was increasing steadily. The United States was the most productive country, while Universite libre de Bruxelles, University of Toronto and University of Geneva were the most active institutions. Diabetes published the most beta-cell studies and received the largest number of co-citations. Decio I Eizirik published the most papers and had the most co-citations. Twelve references on reviews and mechanisms were regarded as the knowledge base. Four major aspects of beta-cell research included the pathological mechanism of beta-cell failure, the recovery of beta cells, the risk factor related to beta cells and the physiology of beta cells. Endoplasmic reticulum stress and oxidative stress have been core elements throughout the research in this field. In addition, beta-cell dedifferentiation, inflammation, autophagy, miRNA, and lncRNA are hot topics nowadays. Additionally, stem cell replacement therapies might be the alternative way to reverse beta-cell failure. Restoring beta-cell mass and function will remain a research goal in the future. Conclusion: This study provided a comprehensive overview of beta-cell research through bibliometric and visual methods. The information would provide helpful references for scholars focusing on beta cells.